Disparities in Antenatal Care Visits between Urban and Rural Ethiopian Women - Senahara Korsa Wake; Abera Botore; Ahmed Mohammed; Kolato Gemede; Moyata Bariso; Urge Gerema (Journal of Pregnancy)
Background. Utilizing antenatal care is one of the best ways to identify issues that are already present or could arise throughout pregnancy. Despite increased efforts to expand health services and antenatal care utilization, less is known regarding antenatal care disparities across different population segments. Therefore, the purpose of this study was to assess the degree of discrepancies between urban and rural Ethiopian pregnant women’s use of antenatal care. Methods. A total sample of 3927 women who gave birth to living children between 2014 and 2019 was included in the study from the 2019 Ethiopia Mini Demographic and Health Survey. Negative binomial Poisson’s regression was adopted to analyze the data. Results. The majority of pregnant women (73.8%) attend at least one antenatal care. Pregnant women in rural areas visited fewer number of antenatal care (68.36%) than those in urban areas (90.1%). Women with age range of 30-40 (IRR: 4.56, 95% CI: 1.07-19.34), women with attending incomplete primary education (IRR: 0.05, 95% CI: 0.02-0.12), women with attending complete primary education (IRR: 0.17, 95% CI: 0.07-0.42), women from middle-income households (IRR: 0.12, 95% CI: 0.06-0.24), women from richer household (IRR: 0.26, 95% CI: 0.14,0.5), women from the richest household (IRR: 0.45, 95% CI: 0.24-0.86), and pregnant women from rural areas (IRR: 0.615, 95%: 0.56-0.67) were observed to be linked with the frequency of antenatal care visits. Conclusion. In Ethiopia, three-fourths of pregnant women attend at least one antenatal care. Place of residence, educational attainment, age in five years’ group, and wealth index for urban/rural were related to the frequency of antenatal care visits.